1990
DOI: 10.1016/0014-5793(90)81499-e
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 induces rapid and transient expression of the c‐fos proto‐oncogene in isolated pancreatic islets and in purified β‐cells

Abstract: The effect of interleukin-lfl (IL-I) on expression of c-fos mRNA in isolated rat pancreatic islets was examined. Accumulation of c-fos mRNA was demonstrable after 30 min of exposure to IL-1, peaked by 60 min, and declined thereafter. Fluorescence-activated cell sorting (FACS) of dispersed islet cells was employed to localize the accumulation of c-fos mRNA to the fl-cell. Cycloheximide did not influence the induction of c-fos mRNA by IL-1. Accumulation of c-fos mRNA therefore appears to be an early signal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In this context, it is noteworthy that treatment of islet cells with cytokines (e.g. interleukin l-~) leads to a rise in cGMP [29] and an increase in c-fos expression [30,31]. The temporal relationship between these events requires further study but the possibility should not be excluded that cGMP may be central to the cytotoxic actions of cytokines in islet cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, it is noteworthy that treatment of islet cells with cytokines (e.g. interleukin l-~) leads to a rise in cGMP [29] and an increase in c-fos expression [30,31]. The temporal relationship between these events requires further study but the possibility should not be excluded that cGMP may be central to the cytotoxic actions of cytokines in islet cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that PKG can regulate gene expression, and among others, it activates c-fos, an early gene that is often expressed in cells undergoing apoptosis (35). Data showing that IL-1␤ induces expression of c-fos in rat islets and in purified rat ␤-cells (36,37) favor this suggestion.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that FOS/JUN activation is involved in cytokine and mechanical stress-induced beta cell death (Abdelli et al, 2007; Hughes et al, 1990) and amylin-induced apoptosis (Zhang et al, 2002). Here, we found that CDKAL1 −/− mediated activation of the FOS/JUN pathway through fatty acids may be a further effector of FOS/JUN regulated beta cell survival, providing mechanistic insight into how CDKAL1 locus may contribute to diabetes progression.…”
Section: Discussionmentioning
confidence: 99%